Prediction of Burnout and Work Engagement of Teachers Based on Job Demands–Resources Model - Zubić, Ivana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The aim of this study was to examine the relationship between elements of the JD-R Model in a sample of teachers from the Republic of Serbia. The sample consisted of 119 teachers who have been working in primary and secondary schools. Work overload was measured by the Workload Scale (Shirom et al., 2010), emotional demands and social support of chiefs were examined by appropriate parts of the Questionnaire on the Experience and Assessment of Work (Van Veldhoven & Meijman, 1994), burnout at work was measured using the Copenhagen Burnout Inventory (CBI), engagement was tested by the UWES – Utrecht Work Engagement Scale (Schaufeli & Bakker, 2004). The results showed statistically significant correlations between work overload, on the one hand, and burnout (r = .570, p
Keywords: job demands; job resources; burnout; job engagement; teachers